The Peasantry as a Class in the Philippine Context - Tadem, Eduardo Climaco (Philippine Social Sciences Review; Volume 64, No. 1, Jan-Jun 2012, Ed. Eric Manalastas, 2012)
This paper attempts to use a modified definition of the peasantry based on (1) a non-traditional reconfiguration of the concept based on a more flexible and less rigid definition of the category, and (2) field data from three rural villages in the Central Luzon region in the Philippines. This more nuanced definition is the result of an interrogation of the various interpretations of class among scholars and thinkers from various Left traditions with respect to the agrarian sector in general and the peasantry in particular. The proposed configuration of the peasantry as a class covers not just the relationship to the means of production but also taking into account the political, social, and cultural aspects of intra-class and inter-class relationships in agrarian societies. The paper then proceeds to apply the redefinition of the peasant class within the context of the field research area’s socio-historical narrative.
Keywords: peasantry, social class